Recommendations From Black Sexual Minority Men: Building Trust to Improve Engagement and Impact of HIV/STI Research. Issue 3 (May 2021) - Grieb, Suzanne M.; Jackman, Kevon-Mark; Tilchin, Carla; Clark, Charles; Sawyer, Simone; Rives, Sarah; Childs, LaNisha; Jennings, Jacky M.
As demonstrated by the consistently documented disproportionately high rates of HIV and STIs (sexually transmitted infections) among Black sexual minority men (BSMM), current efforts to develop responsive interventions to reduce HIV and other STIs within this population have not been sufficient. It is therefore critical that public health researchers reflect meaningfully on the ways in which they investigate HIV and STIs. Engagement with BSMM is crucial in addressing the disproportionately high rates of HIV and STIs experienced, and thus the goal of the current research was to identify community-developed strategies that may enhance community engagement in research with BSMM. Seven focus groups ( N = 38) were held with cisgender BSMM ages 18 to 45 years in Baltimore, Maryland to explore how to better engage this population and improve HIV and STI research. Data analysis of the text was conducted using an iterative, thematic constant comparison process informed by grounded theory. Four distinct themes related to trust-building within the broader community emerged: (1) authentic engagement with the community, (2) increased transparency of the research process, (3) capacity building of research staff from the community, and (4) a balance of research and action. Strategies for researchers to build community trust were identified that are related to, but slightly distinct from, common discussions in the community engaged research literature that are centered more specifically on trust-building within community–academic partnerships. Engagement with BSMM is crucial in addressing HIV and STI health disparities. It is critical that community engagement also be a priority to policy makers, research institutions, and funding institutions.